High-conductivity hybrid filler, silicone rubber composition and preparation method

Through electrostatic adsorption and additive adsorption technology, the surface of the composite filler is dispersed in silicon rubber, covering hybrid fillers with carbon nanomaterials, which solves the problems of complex and low efficiency of the preparation process of high-conductivity hybrid fillers in the prior art, and achieves high conductivity and good mechanical properties.

CN119751981APending Publication Date: 2025-04-04ZHEJIANG XINAN CHEM IND GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410758071.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has problems such as complex process, low efficiency, difficulty in mass production and large-scale solvent production in the preparation of highly conductive hybrid fillers.

Method used

The composite filler surface is obtained by electrostatic adsorption and additive adhesion, and hybrid filler with carbon nanomaterials is uniformly dispersed in silicon rubber. A high-speed disperser and conductive filler treatment agent are used to assist in the coating and dispersion.

Benefits of technology

While reducing the amount of conductive filler, the conductive paths in the silicone rubber mixing rubber system are perfect and stable, ensuring the conductive properties of conductive silicone rubber while improving the mechanical properties of silicone rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004890127060000091
    Figure BDA0004890127060000091
  • Figure BDA0004890127060000101
    Figure BDA0004890127060000101
Patent Text Reader

Abstract

The invention provides a high-conductivity hybrid filler and a silicone rubber composition and a preparation method thereof, and the preparation method comprises the following steps: compounding and hybridizing two or more than two conductive fillers, pre-treating the conductive fillers, and adding the treated conductive fillers into a silicone rubber mixing system to prepare conductive silicone rubber. According to the high-conductivity hybrid filler provided by the invention, the hybrid filler in which the surface of the composite filler is coated with the carbon nano material is obtained through electrostatic adsorption and auxiliary adhesion, and a conductive path in a silicone rubber compound system is perfect and stable while the consumption of the conductive filler is reduced; the mechanical property of the silicone rubber is improved while the conductivity of the conductive silicone rubber is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive silicone rubber, and in particular relates to a highly conductive hybrid filler and a silicone rubber composition thereof and a preparation method thereof. Background Art

[0002] With the innovation of communication technology and the advent of the 5G era, the development of terminal devices such as VR / AR, driverless cars, smart wearables, and flexible electronics has been promoted, broadening the application scenarios of conductive silicone rubber. Conductive silicone rubber is a composite material with excellent conductive properties and environmental sealing functions prepared by adding conductive fillers to the silicone rubber matrix and then through vulcanization, hot pressing molding, injection molding and other processes.

[0003] Currently, commonly used conductive fillers are mainly divided into carbon type, metal type and composite type.

[0004] The carbon atoms in carbon-based conductive fillers are connected by covalent bonds to form a two-dimensional planar structure. There are free-moving electrons on the carbon atoms to achieve conductivity. The main types of carbon black, graphite, carbon fiber, carbon nanotubes, graphene, etc. Among them, carbon black is widely used due to its low price, small addition amount and good conductivity. However, due to the presence of carbon black surface active groups, large particle size and low aspect ratio, its application as a high conductive filler is limited, and the increase in the addition amount will seriously affect the mechanical properties of silicone rubber materials. Therefore, the emergence of carbon nanotubes and graphene fills the gap in the field of carbon-based conductive fillers in high conductive materials. Carbon nanotubes and graphene have high aspect ratios, large specific surface areas and very small amounts of surface active groups, which make them very conductive. A high conductive silicone rubber material can be obtained by adding a small amount to silicone rubber. However, the poor affinity of carbon materials to silicone rubber matrix limits the uniform dispersion and addition amount of carbon materials in silicone rubber. The surface modification of carbon materials using silane coupling agents and other methods to improve their affinity with silicone rubber can increase the addition amount of carbon materials, but at the same time it will lead to a significant decrease in the mechanical properties of silicone rubber materials. This also limits the practical application of highly conductive silicone rubber materials obtained by adding carbon-based conductive fillers alone to the silicone rubber matrix.

[0005] Metals are a type of material that conducts electricity by combining metal atoms with metallic bonds, and sharing free electrons in the outer layer that move freely under an external electric field. They mainly include gold, silver, copper, nickel, etc. in fine powder, flake, foil, or fiber form. Gold has excellent conductivity but is expensive, so it is only used in special occasions. Silver has better conductivity than gold and is relatively cheaper than gold. For conductive silicone that has high conductivity requirements and no cost concerns, silver is an ideal conductive filler. Nickel has a slightly worse conductivity than silver, but is much cheaper. It is a more suitable choice for conductive silicone that has high conductivity and cost pressure.

[0006] In order to reduce costs and obtain relatively high conductivity at the same time, electroplating, chemical plating, spraying and other methods are generally used to cover a layer of highly conductive metal on the surface of materials with low price and conductivity. The substrate inside can be metal (nickel, copper, aluminum, etc.) or non-metal (glass beads, graphite, carbon fiber, ceramics, etc.). However, electroplating requires professional equipment, and the process is complex and energy-intensive; chemical plating will have problems such as uneven coating thickness and poor reproducibility of electrical properties due to unstable process, and a large amount of solvent will be generated during the experiment; surface spraying will cause the metal to be sprayed layer to be loosely bonded, resulting in the metal layer falling off. At present, conductive silicone rubber materials are mainly obtained by purchasing composite conductive fillers with stable performance and adding them to the silicone rubber matrix.

[0007] The composite type is a conductive material metallized on the surface of a non-metallic substrate, mainly including silver-plated glass beads, nickel-plated graphite powder, nickel-plated carbon fiber, silver-plated ceramics, etc. It can reduce the density and cost of conductive materials while improving conductivity. If the carbon-based conductive material is used as a substrate, the two filler conductive mechanisms can be comprehensively utilized to add to the substrate to form a conductive path. This is also the most commonly used type of conductive filler in conductive silicone rubber. However, if the flaky or spherical composite conductive filler wants to build a dense conductive network in the silicone rubber matrix, it also needs a conductive filler with a high specific surface area as a bridge. Nanocarbon materials with high aspect ratio / high specific surface area can be used with composite conductive fillers in the silicone rubber matrix to achieve the construction of a dense conductive network. The composite conductive filler and the nanocarbon material with aspect ratio / high specific surface area are directly added to the silicone rubber matrix. Due to the extremely small size of the carbon-based nanomaterial, it is easy to be embedded in the silicone rubber matrix when directly added to the silicone rubber, resulting in the conductive path between the fillers being cut off. The conductive hybrid filler formed by pre-treating the two fillers to form a composite filler surface coated with nanocarbon materials can avoid the above problems.

[0008] At present, the preparation methods of highly conductive hybrid fillers mainly include solvent method, high temperature pressing method, ball milling method, etc.:

[0009] The solvent method is a commonly used method for hybridizing conductive fillers. It uses anionic or cationic surfactants to achieve hybridization between conductive fillers through electrostatic adsorption, but the solvent method will produce a large amount of solvent.

[0010] 1. The solvent method is a commonly used method for hybridizing conductive fillers. The conductive fillers are hybridized by electrostatic adsorption through anionic or cationic surfactants, but the solvent method will produce a large amount of solvent.

[0011] 2. The high-temperature pressing method is to pre-disperse the carbon material on the metal surface, then micro-melt the metal surface at high temperature to embed the carbon material into the metal surface, and finally fix it at high pressure to obtain a hybrid conductive filler. This method requires specific equipment support and is not universal.

[0012] 3. Ball milling is also a commonly used method for hybrid fillers. Add the conductive filler to be hybridized into the ball mill, and choose wet or dry ball milling according to actual needs. However, ball milling equipment is generally large, requiring a large amount of raw materials for one test, and has low work efficiency and high energy consumption. The large shear force of ball milling may cause the raw materials to be crushed or the surface coating of the composite conductive filler to fall off.

[0013] In summary, in the prior art, the conventional methods for obtaining highly conductive hybrid fillers are solvent method, high temperature pressing method and ball milling method, etc. However, the traditional technical methods still have problems such as the generation of a large amount of solvents, the limitation of professional equipment and low working efficiency.

[0014] For example, Chinese Patent Publication No. CN11961347A mentions in the invention content that the current is conducted by means of the mutual contact or proximity between conductive filler particles or fibers, and that the dispersion in the silicone rubber matrix is ​​an important factor affecting the conductivity.

[0015] Chinese patent publication number CN108948529A provides a method of hybridizing carbon nanotubes modified by cationic surfactant adsorption with carbon black with negative charge on the surface through electrostatic adsorption, filtering to obtain filter residue, and then crushing to obtain composite conductive filler after drying. Multi-walled carbon nanotubes need to be pretreated with hydrofluoric acid and nitric acid to remove part of the amorphous carbon in the carbon nanotubes, and then a nickel film is plated on the surface of the carbon nanotubes through sputtering film forming technology. The hydrofluoric acid and nitric acid used in the process are highly oxidizing and acidic, and the pretreatment process has a greater risk. A large amount of solvent will also be generated during hybridization of fillers. Industrialization needs to consider the post-treatment of waste liquid, which increases environmental protection and cost pressures.

[0016] Chinese patent publication number CN 111548629A discloses a method for preparing conductive rubber for 5G communication base stations, which is to chemically modify carbon fiber cloth to form carbon fiber, then chemically plate the surface to obtain metal-coated carbon fiber, and finally apply silica gel dispersed with carbon nanotubes to the surface of carbon fiber for hot pressing. This patent combines carbon fiber that has been chemically nickel-plated with carbon nanotubes pre-dispersed in silica gel to achieve conductivity. The carbon nanotubes in the silica gel will be partially embedded in the silica gel, and the carbon nanotubes that actually act on the nickel-plated carbon fiber will be damaged. In addition, the preparation of conductive fillers requires chemical plating, chemical modification of carbon fiber cloth and other processes, which are relatively cumbersome, and produce a large amount of solvent while affecting production efficiency.

[0017] Chinese patent publication number CN109637740A uses carbon nanotubes as a matrix and mixes them with zinc sulfate by ball milling. The zinc ions on the surface of the carbon nanotubes are converted into nano zinc oxide by high temperature, and basic groups and silicon elements are grafted onto the surface of the carbon nanotubes under the action of the mixed gas. Ball milling will cause the carbon nanotubes to break and reduce their aspect ratio. Although grafting the surface of the carbon nanotubes can improve their compatibility and dispersibility in the silicone rubber matrix, it will reduce the conductivity of the carbon nanotubes, which is not conducive to the preparation of high-conductivity composite fillers.

[0018] Chinese patent publication number CN112981398A discloses a method for preparing a metal-carbon nanotube film composite material, wherein carbon nanotubes are laid flat on the surface of a metal substrate, a roller press is used to tightly fit the carbon nanotube film on the surface of the metal substrate, and then the carbon nanotube film is placed in a high-temperature furnace at 500-600°C for 1-3 hours to form a solid solution at the contact surface of the carbon nanotube film and the metal substrate. This method is simple in process but requires a professional roller press and a high-temperature furnace to achieve.

[0019] Chinese patent publication number CN101176915A dissolves nickel precursor and polymer resin in an organic solvent in proportion, mixes them evenly, evaporates the solvent, and then places them in an inert or reducing gas at 300-1000°C for carbonization for 1-4 hours to obtain carbon-coated nano-metal nickel particle materials. This method can select different precursors to prepare carbon-coated single or multiple nano-metal particle materials, but the process is cumbersome and inefficient, and it needs to be placed in a specific device to carbonize the polymer resin. In addition, the conductivity of the carbide has certain limitations, which cannot meet the requirements of high conductive fillers to a certain extent. Summary of the invention

[0020] The technical problem to be solved by the present invention is that the conventional means of obtaining highly conductive hybrid fillers is to use solvent method, ball milling method, high temperature pressing method, etc. to hybridize two or more conductive fillers, but traditional technical means still have problems such as complex process, low efficiency, difficulty in large-scale production and generation of a large amount of solvent.

[0021] Therefore, in order to solve the above problems, the present invention provides a highly conductive hybrid filler and a silicone rubber composition and a preparation method thereof. The highly conductive hybrid filler provided by the present invention is a hybrid filler in which a composite filler surface is coated with a carbon-based nanomaterial by electrostatic adsorption and additive adhesion. The present invention reduces the amount of conductive filler while making the conductive path in the silicone rubber compound system perfect and stable, thereby ensuring the conductive properties of the conductive silicone rubber while improving the mechanical properties of the silicone rubber.

[0022] In order to achieve the above object, the present invention adopts the following technical solutions:

[0023] The present invention first provides a high-conductivity hybrid filler, which comprises a composite hybrid of two or more conductive fillers, wherein a composite conductive filler with a larger size of micrometer level and a positively charged surface and a carbon-based nano conductive filler with a smaller size of nanometer level and a negatively charged surface are used in combination, and the mass ratio of the carbon-based nano conductive filler to the composite conductive filler is 1:30-200.

[0024] In the present invention, two or more conductive fillers are selected for composite hybridization, and the advantages of different conductive fillers are combined to synergistically improve the conductivity. The present invention pre-treats the conductive filler, weighs a certain amount of carbon-based nano-conductive fillers and composite conductive fillers of different particle sizes, adds a conductive filler treatment agent, grinds them in a mortar for 15 minutes for pre-dispersion, and then puts them into a high-speed disperser with a rotation speed of 1000-80000rpm for dispersion for 2-10 minutes. During high-speed friction, the metal on the surface of the composite conductive filler easily loses electrons, resulting in a positive charge on the surface, and the surface of the carbon-based nanomaterial is negatively charged. Therefore, the carbon-based nanomaterial is easily coated on the surface of the composite conductive filler through high-speed friction to obtain a hybrid conductive filler. The added conductive filler treatment agent not only helps the carbon nanomaterial to coat the composite conductive filler, but also facilitates the uniform dispersion of the hybrid conductive filler in the silicone rubber.

[0025] When hybridizing conductive fillers, adding conductive filler treatment agents and using high-speed dispersers assist in the coating of composite fillers with carbon nanomaterials, and also facilitate the uniform dispersion of hybrid conductive fillers in silicone rubber. The process is simple to operate, does not produce solvents, and can be continuously mass-produced.

[0026] As a preferred embodiment of the present invention, the carbon nanofiller includes at least one of graphene and carbon nanotubes, wherein the graphene is a single layer or a few layers of graphene with a specific surface area of ​​200 m 2 / g; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5-50nm and a length of 1-20μm, and an aspect ratio of ≥100.

[0027] As a preferred embodiment of the present invention, the composite filler includes at least one of silver-plated aluminum powder, silver-plated nickel powder, nickel-coated graphite powder, and nickel-coated carbon fiber, and the average particle size of the composite conductive filler is 5-150 μm.

[0028] The present invention also provides a silicone rubber composition containing the above-mentioned highly conductive hybrid filler, wherein the silicone rubber composition comprises, by weight, 100 parts of methyl vinyl silicone rubber raw rubber, 0.5-40 parts of carbon-based conductive filler, 40-500 parts of composite conductive filler, 2-40 parts of white carbon black, 1-20 parts of a structuring control agent, 1-20 parts of a conductive filler treatment agent, and 0.5-3 parts of a vulcanizing agent.

[0029] In the present invention, the expansion and upgrading of the application scenarios of conductive silicone rubber materials have increased the requirements for their electrical and mechanical properties, requiring them not only to have extremely low volume resistivity (≤0.1Ω*cm), but also to have good tensile strength, sealing, aging resistance, oil resistance and other properties.

[0030] As a preferred solution of the present invention, the molar percentage of vinyl in the silicone rubber is 0.02%-0.3%, and the viscosity average molecular weight is 550,000-1.3 million.

[0031] As a preferred embodiment of the present invention, the white carbon black is at least one of precipitated white carbon black and fumed white carbon black, wherein the precipitated white carbon black has a specific surface area of ​​50 m 2 / g-300m 2 / g, fumed silica specific surface area 100m 2 / g-400m 2 / g.

[0032] As a preferred embodiment of the present invention, the structuring control agent is at least one of hydroxy silicone oil, hydroxy fluorosilicone oil, vinyl silazane, hexamethyldisilazane, diphenyldihydroxysilane, and octamethylcyclotetrasiloxane.

[0033] As a preferred embodiment of the present invention, the conductive filler treating agent is at least one of the silane coupling agents vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0034] As a preferred embodiment of the present invention, the vulcanizing agent is at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,4-dichlorobenzoyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, diisopropylbenzene peroxide and di-tert-butyl peroxide.

[0035] Finally, the present invention provides a method for preparing the silicone rubber composition, which comprises the following steps:

[0036] S1: Hybrid conductive filler: weigh carbon conductive filler and composite conductive filler with different particle sizes, add conductive filler treatment agent and grind for pre-dispersion, and disperse at a speed of 1000-80000rpm for 2-10min;

[0037] S2: Weigh the silicone rubber raw rubber, white carbon black and structure control agent, put them into a kneader, put the white carbon black into the kneader in 1-3 times, control the temperature to ≤80°C throughout the process, knead for 30-45 minutes and mix evenly to obtain the silicone rubber base;

[0038] S3: adding 80-300 parts of the hybrid conductive filler prepared in step S1 to the silicone rubber base of step S2 in 3-4 times, kneading for 15 minutes each time and controlling the material temperature during kneading to be ≤80°C, and kneading for 20 minutes after the addition is completed, and then placing the mixture on an open mill with a roller distance of 1mm to obtain a thin sheet, and baking it in a 110°C forced air oven for 3 hours to remove low molecular weight, thereby obtaining a silicone rubber composition;

[0039] S4: After the silicone rubber composition of step S3 is cooled, it is placed on an open mill, and after being rolled, a vulcanizing agent is added, and after being thinned through 5-10 times, the sheet is removed, placed in a mold of a fixed size, and molded to obtain a highly conductive silicone rubber sheet;

[0040] S5: placing the highly conductive silicone rubber sheet obtained in step S4 in a blast oven for two-stage vulcanization treatment to obtain a highly conductive silicone rubber material.

[0041] In the present invention, the silicone rubber composition adopts kneading and low-temperature baking processes. The shorter kneading process will not destroy the conductive overlap of the constructed hybrid conductive filler. The low-temperature baking does not require a high-temperature re-refining process, which prevents the conductivity from decreasing. At the same time, it makes up for the problem of poor compatibility between the conductive filler and the silicone rubber matrix due to the short kneading time.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1) The highly conductive hybrid filler provided by the present invention is a hybrid filler in which the surface of the composite filler is coated with carbon nanomaterials through electrostatic adsorption and auxiliary agent adhesion. Unhybridized fillers are easily embedded in the silicone rubber base glue due to the extremely small size of carbon nanomaterials, resulting in the interruption of the conductive path between fillers. However, the hybridized filler pre-distributes the carbon nanomaterials on the surface of the composite filler. Adding the base glue system not only avoids the embedding of carbon nanomaterials, but also the carbon nanofillers with high aspect ratio can serve as a bridge to connect the conductive path of the composite filler, reducing the amount of conductive filler while making the conductive path in the silicone rubber compound system perfect and stable, ensuring the conductive properties of the conductive silicone rubber while improving the mechanical properties of the silicone rubber.

[0044] 2) The conductive fillers of the present invention are selected in two or more types and two of them have opposite charges on their surfaces instead of having the same charge. When hybridizing the conductive fillers, electrostatic adsorption will occur because the surfaces of the two conductive fillers have opposite negative charges.

[0045] 3) The present invention selects at least two conductive fillers with sizes that differ by one order of magnitude, rather than selecting conductive fillers with sizes of the same order of magnitude. Nano-scale conductive fillers are also easily adsorbed on the surface of larger micron-scale conductive fillers to achieve hybridization.

[0046] 4) When the hybrid conductive filler of the present invention is added with a conductive filler treatment agent and used in conjunction with a high-speed disperser to assist the carbon nanomaterial in coating the composite filler, and also facilitate the uniform dispersion of the hybrid conductive filler in the silicone rubber. The process is simple to operate, does not produce solvents, can be continuously mass-produced, and is not limited to the application in the field of silicone rubber. The hybrid conductive filler can be added to other polymer materials for application.

[0047] 5) The silicone rubber composition of the present invention adopts a preparation method of short-time kneading and mixing and low-temperature baking post-treatment, rather than the kneading and mixing of common mixed rubbers and vacuum refining at elevated temperature. The shorter kneading process will not destroy the conductive overlap of the constructed hybrid conductive filler, and the low-temperature baking without high-temperature refining process prevents the decrease of conductive performance, while compensating for the problem of poor compatibility between the conductive filler and the silicone rubber matrix due to the short kneading time.

[0048] 6) The expansion and upgrading of the application scenarios of the conductive silicone rubber material of the present invention have increased the requirements for its electrical and mechanical properties. It is not only required to have an extremely low volume resistivity (≤0.1Ω*cm), but also required to have good tensile strength, sealing, aging resistance and oil resistance. The present invention can also select suitable raw rubber according to actual needs with corresponding structural control and conductive filler treatment agents to expand its application in the automotive industry, consumer electronics, low temperature resistance, aging resistance and other fields. DETAILED DESCRIPTION

[0049] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] This embodiment provides a highly conductive hybrid filler and a silicone rubber composition thereof, comprising the following raw materials in parts by weight: 70 parts by weight of silicone rubber raw rubber with a vinyl content of 0.3% and 30 parts by weight of silicone rubber raw rubber with a vinyl content of 0.02% (the viscosity-average molecular weight of the silicone rubber raw rubber is 80,000), with a specific surface area of ​​200 m 2 / g of fumed silica 10 parts by weight, 180 parts by weight of nickel-coated graphite powder with an average size of 100μm, 60 parts by weight of nickel-coated graphite powder with an average size of 40μm, 2 parts by weight of multi-walled carbon nanotubes with a diameter of 9.5nm and a length of 1.5μm (the mass ratio of carbon nanofiller: metal conductive filler is 1:120), 6 parts by weight of hydroxy silicone oil, 1 part by weight of methoxy silicone oil, and 2 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560).

[0052] The method for preparing the highly conductive hybrid filler and the silicone rubber composition thereof in this embodiment comprises the following steps:

[0053] S1: Hybrid conductive filler: 2 parts of multi-walled carbon nanotubes and 240 parts of nickel-coated graphite powder (180 parts with an average size of 100 μm and 60 parts with an average size of 40 μm), 4 parts of hydroxy silicone oil and 2 parts of KH560 were weighed and ground in a mortar for 15 minutes for pre-dispersion, and then dispersed in a high-speed disperser at a speed of 8000 rpm for 8 minutes;

[0054] S2: Weigh 70 parts of silicone rubber with a vinyl content of 0.3%, 30 parts of silicone rubber with a vinyl content of 0.02%, 10 parts of fumed silica, 2 parts of hydroxy silicone oil, and 1 part of methoxy silicone oil, put all of them into a kneader, knead and mix them evenly for 30 minutes, and control the material temperature to ≤80°C to obtain a silicone rubber base;

[0055] S3: Add 242 parts of the hybrid conductive filler prepared in step S1 to the silicone rubber base of step S2 in 4 times, knead for 15 minutes each time and control the material temperature during kneading to be ≤80°C. After the addition is completed, continue kneading for 20 minutes to mix evenly, place on an open mill with a roller distance of 1mm to obtain a thin sheet, and bake in a 110°C forced air oven for 3 hours to remove low molecular weight, to obtain a silicone rubber composition;

[0056] S4: After the silicone rubber composition of step S3 is cooled, it is placed on an open mill, and after being rolled, 1.5 parts of 2,5-dimethyl-2,5-bis(di-tert-butylperoxy)hexane is added, and after being thinned 10 times, the sheet is removed, and hot-pressed in a mold at a temperature of 170° C. and a pressure of 15 MPa for 10 minutes to obtain a highly conductive silicone rubber sheet;

[0057] S5: The highly conductive fluorosilicone sheet obtained in step S4 is placed in a 200° C. forced air oven for two-stage vulcanization for 4 hours to obtain a highly conductive silicone rubber material.

[0058] Example 2

[0059] This embodiment provides a highly conductive hybrid filler and a silicone rubber composition thereof, comprising the following raw materials in parts by weight: 75 parts by weight of silicone rubber raw rubber with a vinyl content of 0.23% and 25 parts by weight of silicone rubber raw rubber with a vinyl content of 0.02% (the viscosity-average molecular weight of the silicone rubber raw rubber is 890,000), with a specific surface area of ​​130 m 2 / g of precipitated silica 10 parts by weight, 100 parts by weight of nickel-coated graphite powder with an average size of 100μm, 40 parts by weight of silver-plated nickel powder with an average size of 25μm, 1.6 parts by weight of multi-walled carbon nanotubes with a diameter of 9.5nm and a length of 1.5μm (the mass ratio of carbon nanofiller: metal conductive filler is 1:187.5), 6 parts by weight of hydroxy silicone oil, 1 part by weight of methoxy silicone oil, 1 part by weight of vinyl triethoxy silane and 3 parts by weight of γ-(2,3-epoxypropoxy)propyl trimethoxy silane (KH560).

[0060] The method for preparing the highly conductive hybrid filler and the silicone rubber composition thereof in this embodiment comprises the following steps:

[0061] S1: Hybrid conductive filler: 220 parts of nickel-coated graphite powder with an average size of 100 μm, 80 parts of silver-coated aluminum powder with an average size of 25 μm, 1.6 parts of multi-walled carbon nanotubes with a tube diameter of 9.5 nm and a tube length of 1.5 μm, 4 parts of hydroxy silicone oil, 1 part of vinyl triethoxysilane and 3 parts of KH560 were weighed and put into a mortar and ground for 15 minutes for pre-dispersion, and then put into a high-speed disperser with a rotation speed of 8000 rpm for dispersion for 8 minutes;

[0062] S2: Weigh 70 parts of silicone rubber with a vinyl content of 0.3%, 30 parts of silicone rubber with a vinyl content of 0.02%, and 10 parts of silicone rubber with a specific surface area of ​​130 m 2 / g of precipitated silica, 2 parts of hydroxy silicone oil and 1 part of methoxy silicone oil were all put into a kneader and kneaded for 30 minutes to obtain a silicone rubber base;

[0063] The remaining preparation method is the same as in Example 1.

[0064] Example 3

[0065] This embodiment provides a highly conductive hybrid filler and a silicone rubber composition thereof, comprising the following raw materials in parts by weight: 70 parts by weight of trifluoropropyl methyl vinyl silicone rubber raw rubber with a vinyl content of 0.3% and 30 parts by weight of trifluoropropyl methyl vinyl silicone rubber raw rubber with a vinyl content of 0.02% (the viscosity-average molecular weight of the trifluoropropyl methyl vinyl silicone rubber raw rubber is 1.2 million), a specific surface area of ​​200 m 2 / g of fumed silica 10 parts by weight, 165 parts by weight of nickel-coated graphite powder with an average size of 100μm, 60 parts by weight of nickel-coated graphite powder with an average size of 40μm, 3 parts by weight of multi-walled carbon nanotubes with a diameter of 9.5nm and a length of 1.5μm (the mass ratio of carbon-based nanofiller:metal-based conductive filler is 1:75), 6 parts by weight of hydroxyfluorosilicone oil, 3 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), 3 parts by weight of hexamethyldisilazane, and 0.4 parts by weight of deionized water.

[0066] The method for preparing the highly conductive hybrid filler and the silicone rubber composition thereof in this embodiment comprises the following steps:

[0067] S1: Hybrid conductive filler: 3 parts of multi-walled carbon nanotubes, 165 parts of nickel-coated graphite powder with an average size of 100 μm, 60 parts of nickel-coated graphite powder with an average size of 40 μm, 4 parts of hydroxy fluorosilicone oil and 3 parts of KH560 were weighed and put into a mortar and ground for 15 minutes for pre-dispersion, and then put into a high-speed disperser with a rotation speed of 8000 rpm for dispersion for 8 minutes;

[0068] S2: Weigh 70 parts of trifluoropropyl methyl vinyl silicone rubber with a vinyl content of 0.3%, 30 parts of trifluoropropyl methyl vinyl silicone rubber with a vinyl content of 0.02%, 10 parts of fumed silica, 2 parts of hydroxy fluorosilicone oil, 1 part of hexamethyldisilazane and 0.15 parts of deionized water, put all of them into a kneader and knead for 30 minutes to obtain a silicone rubber base;

[0069] S3: Add the remaining 2 parts of hexamethyldisilazane and 0.25 parts of deionized water to the silicone rubber base of step S2, and add 228 parts of the hybrid conductive filler prepared in step S1 in 4 times, kneading for 15 minutes each time and controlling the material temperature during kneading to be ≤80°C. After the addition is completed, continue kneading for 20 minutes and mix evenly, then place on an open mill with a roller distance of 1mm to obtain a thin sheet, and bake in a 110°C forced air oven for 3 hours to remove low molecules, to obtain a silicone rubber composition;

[0070] The remaining preparation method is the same as in Example 1.

[0071] Example 4

[0072] The present embodiment provides a highly conductive hybrid filler and a silicone rubber composition thereof, comprising the following raw materials in parts by weight: 70 parts by weight of silicone rubber raw rubber with a vinyl content of 0.3% and 30 parts by weight of silicone rubber raw rubber with a vinyl content of 0.02% (the viscosity-average molecular weight of the silicone rubber raw rubber is 890,000), a specific surface area of ​​130 m 2 / g of precipitated silica 10 parts by weight, 110 parts by weight of nickel-coated graphite powder with an average size of 100μm, 50 parts by weight of nickel-coated graphite powder with an average size of 40μm, 12 parts by weight of multi-walled carbon nanotubes with a tube diameter of 9.5nm and a tube length of 1.5μm (the mass ratio of carbon-based nanofiller to metal-based conductive filler is 1:13.3), 6 parts by weight of hydroxy silicone oil, 10 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), 3 parts by weight of hexamethyldisilazane, 0.4 parts by weight of deionized water, and 0.2 parts by weight of vinylsilazane.

[0073] The method for preparing the highly conductive hybrid filler and the silicone rubber composition thereof in this embodiment comprises the following steps:

[0074] S1: Hybrid conductive filler: 12 parts of multi-walled carbon nanotubes, 110 parts of nickel-coated graphite powder with an average size of 100 μm, 50 parts of nickel-coated graphite powder with an average size of 40 μm, 4 parts of hydroxy silicone oil and 3 parts of KH560 were weighed and put into a mortar and ground for 15 minutes for pre-dispersion, and then put into a high-speed disperser with a rotation speed of 30,000 rpm for dispersion for 10 minutes;

[0075] S2: Weigh 70 parts of silicone rubber with a vinyl content of 0.3%, 30 parts of silicone rubber with a vinyl content of 0.02%, 10 parts of precipitated silica, 2 parts of hydroxy silicone oil, 1 part of hexamethyldisilazane and 0.15 parts of deionized water, put all of them into a kneader and knead for 30 minutes to obtain a silicone rubber base;

[0076] S3: Add the remaining 2 parts of hexamethyldisilazane, 0.25 parts of deionized water and 0.2 parts of vinylsilazane to the silicone rubber base of step S2, and add 172 parts of the hybrid conductive filler prepared in step S1 in 3 times, knead for 15 minutes each time and control the material temperature during kneading to be ≤80°C. After the addition is completed, continue kneading for 20 minutes and mix evenly, then place on an open mill with a roller spacing of 1mm to obtain a sheet, and bake in a 110°C forced air oven for 3 hours to remove low molecules to obtain a silicone rubber composition;

[0077] The remaining preparation method is the same as in Example 1.

[0078] Comparative Example 1

[0079] The difference between Comparative Example 1 and Example 1 is that the conductive filler is directly added to the silicone rubber base and kneaded without undergoing hybridization treatment.

[0080] The raw materials used in Comparative Example 1 are the same as those in Example 1.

[0081] The preparation method of Comparative Example 1 comprises the following steps:

[0082] S1: Weigh 70 parts of silicone rubber with a vinyl content of 0.3%, 30 parts of silicone rubber with a vinyl content of 0.02%, 10 parts of fumed silica, 2 parts of multi-walled carbon nanotubes with a tube diameter of 9.5 nm and a tube length of 1.5 μm, 6 parts of hydroxy silicone oil, and 1 part of methoxy silicone oil, put all of them into a kneader, knead for 30 minutes, and mix them evenly to obtain a silicone rubber base;

[0083] S2: Add 242 parts of nickel-coated graphite powder (180 parts with an average size of 100 μm and 60 parts with an average size of 40 μm) to the silicone rubber base of step S1 in 4 times in the order of large size first and small size later, knead for 15 minutes each time and control the material temperature during kneading to be ≤80°C, continue kneading for 20 minutes after the addition is completed, mix evenly, place on an open mill with a roller distance of 1 mm to obtain a sheet, put into a 110°C forced air oven for baking for 3 hours to remove low molecules, and obtain a silicone rubber composition;

[0084] The remaining preparation method is the same as in Example 1.

[0085] Comparative Example 2

[0086] The difference between Comparative Example 2 and Example 1 is that no multi-walled carbon nanotube material is added, and the preparation method is the same as that of Example 1 except that no multi-walled carbon nanotube is added.

[0087] Comparative Example 3

[0088] The difference between Comparative Example 3 and Example 1 is that the masterbatch is a methyl vinyl silicone rubber raw rubber with a vinyl content of only 0.02%, and the preparation method is the same as that of Example 1.

[0089] Comparative Example 4

[0090] The difference between Comparative Example 4 and Example 1 is that the added conductive filler is only nickel-coated graphite powder with an average size of 100 μm, and the added amount is 300 parts, and the conductive filler does not need to be hybridized. The preparation method is the same as Example 1 except that there is no hybrid conductive filler in step S2.

[0091] The conductive silicone rubber compositions of Examples 1-4 and the silicone rubber materials of Comparative Examples 1-4 were tested for hardness (GB / T531.1-2008), mechanical properties (GB / T 528-2009), and volume resistivity (GB / T 2439-2001). Specific data are shown in Table 1.

[0092] Table 1. Test data

[0093]

[0094]

[0095] As can be seen from Table 1, the mass ratios of carbon nano conductive filler: composite conductive filler in Examples 1-4 are 1:120, 1:187.5, 1:75 and 1:13.3, respectively. The higher the proportion of composite conductive filler, the lower the volume resistivity, but the hardness will increase significantly, and the tensile strength and elongation will decrease significantly.

[0096] Analysis of the data of Example 1 and Comparative Example 1 shows that the treatment method of the hybrid conductive filler can effectively reduce the volume resistivity of the silicone rubber while improving the tensile strength and elongation at break. This is due to the fact that the hybrid filler formed by electrostatic adsorption and additive adhesion forms a composite filler surface coated with carbon nanomaterials to build a complete conductive network in the silicone rubber. In addition, the introduction of nanomaterials can effectively improve the mechanical properties of the silicone rubber material.

[0097] It can be seen from Example 1 and Comparative Examples 2 and 4 that if pure composite fillers want to achieve the conductive effect of carbon-based conductive fillers and metal fillers, the amount of composite fillers added needs to be increased. The increase in the amount of fillers will inevitably affect the processing performance of silicone rubber, increase the hardness and decrease the mechanical properties. At the same time, the compounding of conductive fillers of different sizes can fill the gaps between large-size conductive fillers, and achieve excellent conductive effects and mechanical properties with less total amount of fillers.

[0098] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A highly conductive hybrid filler, characterized in that: The highly conductive hybrid filler comprises a composite hybrid of two or more conductive fillers, wherein a composite conductive filler having a larger size of micrometer level and a positively charged surface and a carbon-based nano conductive filler having a smaller size of nanometer level and a negatively charged surface are used in combination, and the mass ratio of the carbon-based nano conductive filler to the composite conductive filler is 1:30-200.

2. A highly conductive hybrid filler according to claim 1, characterized in that: The carbon nanofiller includes at least one of graphene and carbon nanotubes, wherein the graphene is a single layer or a few layers of graphene, and the specific surface area is ≥200m 2 / g; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5-50nm and a length of 1-20μm, and an aspect ratio of ≥100.

3. A highly conductive hybrid filler according to claim 1, characterized in that: The composite filler comprises at least one of silver-plated aluminum powder, silver-plated nickel powder, nickel-coated graphite powder and nickel-coated carbon fiber. The average particle size of the composite conductive filler is 5-150 μm.

4. A silicone rubber composition, characterized in that: The silicone rubber composition comprises, by weight, 100 parts of methyl vinyl silicone rubber, 0.5-40 parts of carbon-based conductive filler, 40-500 parts of composite conductive filler, 2-40 parts of white carbon black, 1-20 parts of structural control agent, 1-20 parts of conductive filler treatment agent and 0.5-3 parts of vulcanizer.

5. A silicone rubber composition according to claim 4, characterized in that: The molar percentage of vinyl in the silicone rubber raw rubber is 0.02%-0.3%, and the viscosity average molecular weight is 550,000-1.3 million.

6. A silicone rubber composition according to claim 4, characterized in that: The white carbon black is at least one of precipitated white carbon black and fumed white carbon black, wherein the precipitated white carbon black has a specific surface area of ​​50 m 2 / g-300m 2 / g, fumed silica specific surface area 100m 2 / g-400m 2 / g.

7. A silicone rubber composition according to claim 4, characterized in that: The structuring control agent is at least one of hydroxy silicone oil, hydroxy fluorosilicone oil, vinyl silazane, hexamethyldisilazane, diphenyldihydroxysilane, and octamethylcyclotetrasiloxane.

8. A silicone rubber composition according to claim 4, characterized in that: The conductive filler treatment agent is at least one of silane coupling agents selected from vinyl trimethoxy silane, vinyl triethoxy silane, γ-aminopropyl triethoxy silane, and γ-(2,3-epoxypropoxy)propyl trimethoxy silane.

9. A silicone rubber composition according to claim 4, characterized in that: The vulcanizing agent is at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,4-dichlorobenzoyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, diisopropylbenzene peroxide and di-tert-butyl peroxide.

10. A method for preparing a silicone rubber composition, characterized in that: The preparation method comprises the following steps: S1: Hybrid conductive filler: weigh carbon conductive filler and composite conductive filler with different particle sizes, add conductive filler treatment agent and grind for pre-dispersion, and disperse at a speed of 1000-80000rpm for 2-10min; S2: Weigh the silicone rubber raw rubber, white carbon black and structure control agent, put them into a kneader, put the white carbon black into the kneader in 1-3 times, control the temperature to ≤80°C throughout the process, knead for 30-45 minutes and mix evenly to obtain the silicone rubber base; S3: adding 80-300 parts of the hybrid conductive filler prepared in step S1 to the silicone rubber base of step S2 in 3-4 times, kneading for 15 minutes each time and controlling the material temperature during kneading to be ≤80°C, and kneading for 20 minutes after the addition is completed, and then placing the mixture on an open mill with a roller distance of 1mm to obtain a thin sheet, and baking it in a 110°C forced air oven for 3 hours to remove low molecular weight, thereby obtaining a silicone rubber composition; S4: After the silicone rubber composition of step S3 is cooled, it is placed on an open mill, and after being rolled, a vulcanizing agent is added, and after being thinned through 5-10 times, the sheet is removed, placed in a mold of a fixed size, and molded to obtain a highly conductive silicone rubber sheet; S5: placing the highly conductive silicone rubber sheet obtained in step S4 in a blast oven for two-stage vulcanization treatment to obtain a highly conductive silicone rubber material.

Citation Information

Patent Citations

  • Method for preparing nano metallic nickel granular material coating with carbon

    CN101176915A

  • Preparation method for composite conductive plastic

    CN108948529A

  • Preparation method of composite conductive filler

    CN109637740A

  • Conductive rubber for 5G communication base station and preparation method of the conductive rubber

    CN111548629A

  • Metal-carbon nanotube film composite material and preparation method thereof

    CN112981398A